Recreational Facilities for Leisure and Pleasure in Shopping Mall in Pakistan - Reena Majid Memon; Yasira Naeem Pasha; Nazia Iftakhar; Bushra Danish Talpur; Sohrab Ahmed Marri (Sir Syed University Research Journal of Engineering and Technology, 2022)
Shopping is a social activity that takes on many forms in various cultures. The goal of this study is to portray modern shopping as a modified behaviour that is often practiced in shopping malls. It also tries to examine current buying behaviour in light of the recreational facilities available to customers. It refers to the use of a shopping mall for a variety of purposes, including ancillary services. To name a few, there is a food court, a play area, a fitness club, a five-dimensional (5D) movie theater, a Baby Chair, an atrium/exhibition hall, free Wi-Fi, and a cinema hall. These user-based amenities have arisen as distinguishing characteristics of shopping malls, emphasizing a mall's uniqueness. This study focuses on a few recreational facilities and then narrows down to recreational facilities sub-categories at a specific retail mall called Emerald Mall. The data is collected in a quantitative manner and presented statistically, with the findings analyzed using criteria relevant to shopping mall quality as a whole. The findings include the identification of inadequate facilities in the food court, play area, and fitness club. At first, there was a Jest five-dimensional (5D) movie theatre, but now it is not available. Furthermore, a baby chair, an atrium/exhibition hall, free Wi-Fi, and a cinema hall were missing.